Anticoagulation in clinical practice -2nd Part: the use of heparins - Timóteo, Ana Teresa (1998)
The authors review, in this, the second part of the theme "anticoagulation in clinical practice", the use of heparins in clinical practice. First, the use of unfractionated heparin, is discussed its indicated uses in inpatients, with often consequent long in-patient admission times, as well as the disadvantages of its use on the outpatient basis e.g. difficult use at home and complex monitorisation. Secondly, the authors' present low molecular weight heparins, which combine easy administration with easy monitorisation, making their total cost lower than that of unfractionated heparin. Caution must be exercised in their implementation, as each low molecular weight heparin has an individual profile that must be assessed in each clinical situation. To date, all studies point to a beneficial effect with the use of the various unfractionated heparins in their different clinical settings. lt seems probable that new indications will appear.